ChemInform Abstract: Synthesis of Quinazolines via CuO Nanoparticles Catalyzed Aerobic Oxidative Coupling of Aromatic Alcohols and Amidines. Issue 1 (January 2015) - Zhang, Wu; Guo, Fei; Wang, Fei; Zhao, Na; Liu, Liang; Li, Jia; Wang, Zhenghua
Abstract CuO nanoparticles are found to be efficient catalysts for the reaction of N‐arylamidines (I) and (IV) and aromatic aldehydes (II) or benzyl alcohols (VI) to afford quinazolines (III) and (V), resp., in good to high yields.